Multiwavelength study of high-redshift blazars. Issue 2 (17th August 2020) - Sahakyan, N; Israyelyan, D; Harutyunyan, G; Khachatryan, M; Gasparyan, S
ABSTRACT: High-redshift blazars are among the most powerful objects in the Universe. The spectral and temporal properties of 33 distant blazars ( z > 2.5) detected in the high-energy γ-ray band are investigated by analysing the Fermi -LAT and Swift Ultraviolet and Optical Telescope/X-ray Telescope (UVOT/XRT) data. The considered sources have soft time-averaged γ-ray spectra (Γγ ≥ 2.2) whereas those that have been observed in the X-ray band have hard X-ray spectra (ΓX = 1.01−1.86). The γ-ray flux of high-redshift blazars ranges from 4.84 × 10 −10 to 1.50 × 10 −7 photon cm −2 s −1 and the luminosity is within (0.10−5.54) × 10 48 erg s −1 which during the γ-ray flares increases up to (0.1−1) × 10 50 erg s −1 . In the X-ray band, only the emission of PKS 0438−43, B2 0743+25, and TXS 0222+185 is found to vary in different Swift XRT observations whereas in the γ-ray band, the emission is variable for fourteen sources: the flux of B3 1343+451 and PKS 0537−286 changes in sub-day scales, that of PKS 0347−211 and PKS 0451−28 in day scales, while the γ-ray variability of the others is in week or month scales. The properties of distant blazar jets are derived by modelling the multiwavelength spectral energy distributions within a one-zone leptonic scenario assuming that the X-ray and γ-ray emissions are produced from inverse Compton scattering of synchrotron and dusty torus photons. From the fitting, the emission region size is found to be ≤0.05 pc and the magnetic field and the Doppler factor are correspondingly within 0.10−1.74 G and 10.0−27.4. By modelling the optical–UV excess, we found that the central black hole masses and accretion disc luminosities are within L d ≃ (1.09−10.94) × 10 46 erg s −1 and (1.69−5.35) × 10 9 M⊙, respectively.